Percieved Quality Analysis Petani Terhadap Produk Herbisida Kontak Di Kabupaten Lampung Tengah - Yunada Arpan; M Rafiq (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
The competition of Contact Herbicide has been sharper and sharper urging the companiesto give better quality to the farmer actualized by the product attribute. This has been taken to keepthe selling frequency and promote the product amid the consumer through an analysis of perceivedquality so that the product quality bears in mind of the consumers.The researcher suggested the Gramaxone company to redesign all attributes issued in theprevious product model because the PQ relative is only 0, 01 (1%) and is lower if it is compared withthat of all other attributes. At Noxone product, the company need to redesign all product attributescovering content quantity, content of poison, safety in use and cover design.